SISTEM PENGELOLAAN PRAKTIKUM FTI UNTAR BERBASIS WEB DAN MOBILE - Michael Michael; Bobby Tumbelaka (Fakultas Teknologi Informasi Universitas Tarumanagara, 2016)
Online registration application was shown to effect efficient, easy and secure against practicum participants, lectures and admin practicum. This system is regenerated using laravel Framework system and supported using mobile android applications. The results of some test perfomed using several security techniques such as bruteforece, HTTP INJECT and SQL Injection has been done and give good results and this results of security testing for this system mean, this system is enough to prevent the destruction system by “CRACKER” or a person who is not to be repsonsible in addition there is a survei regrading this application. The results of the survei can be said to havebeen able to fullfill design objectives of this applications.